Algunas especies de Passiflora y su capacidad antioxidante (2011)
ABSTRACT: Fruits and vegetables play an important role in the human diet because these foods provide an optimal mix of antioxidants like vitamins C and E, polyphenols and carotenoids which is beneficial for health protection. Objectives: To evaluate the antioxidant capacity, the reducing power and the content of total phenols of some fruit and leaf extracts of Passiflora genus in Huila department. Methods: The antioxidant capacity was measured as the ability to catch the radical 2.2-diphenyl-1-picryl hydrazil (DPPH) and 2'-azino-bis (3-ethylbenzatiazolin-6-ammonium sulphonate (ABTS'+), the ferric reducing antioxidant power (FRAP) and total phenol content were determined using Folin-Ciocalteu´s reagent trial. Results: The extracts demonstrated different degrees of antioxidant capacity. However, leaf extracts exhibited higher antioxidant capacity than the fruit extracts. These variations may be due to high content of reducing agents such as ascorbic acid, minerals and carotenoids, and to genetic and environmental factors of the species. Conclusions: The presence of antioxidants in fruits and substrates from the leaves of some species of Passiflora genus was evinced, especially high significant values were found in wild granadilla fruits and in gulupa leaves.